2020
DOI: 10.1177/1179544120906461
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids in Chronic Non-Cancer Pain: A Systematic Review and Meta-Analysis

Abstract: Background: For patients with chronic, non-cancer pain, traditional pain-relieving medications include opioids, which have shown benefits but are associated with increased risks of addiction and adverse effects. Medical cannabis has emerged as a treatment alternative for managing these patients and there has been a rise in the number of randomized clinical trials in recent years; therefore, a systematic review of the evidence was warranted. Objective: To analyze the evidence surrounding the benefits and harms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 73 publications
2
77
0
3
Order By: Relevance
“…Overall, the greater access to cannabis in North America has led to rapidly increasing interest in the possible benefits and harms surrounding its use. A systematic review and metaanalyses of randomized controlled trials (RCTs) showed that cannabinoids had a statistically significant pain reduction effect compared to placebo among patients with CNCP after a period of treatment of less than 2 weeks (weighted mean difference (WMD) −0.54, 95% confidence interval (CI) −0.76 to −0.31), up to 2 months (WMD −0.68, 95% CI −0.96 to −0.40), and up to 6 months (WMD −0.43, 95% CI −0.75 to −0.10), measured on a 0-10 pain visual analog scale [31]. Furthermore, the movement away from opiates as an analgesic has fuelled an increased interest in applications for cannabinoids in the treatment of chronic noncancer-related pain.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the greater access to cannabis in North America has led to rapidly increasing interest in the possible benefits and harms surrounding its use. A systematic review and metaanalyses of randomized controlled trials (RCTs) showed that cannabinoids had a statistically significant pain reduction effect compared to placebo among patients with CNCP after a period of treatment of less than 2 weeks (weighted mean difference (WMD) −0.54, 95% confidence interval (CI) −0.76 to −0.31), up to 2 months (WMD −0.68, 95% CI −0.96 to −0.40), and up to 6 months (WMD −0.43, 95% CI −0.75 to −0.10), measured on a 0-10 pain visual analog scale [31]. Furthermore, the movement away from opiates as an analgesic has fuelled an increased interest in applications for cannabinoids in the treatment of chronic noncancer-related pain.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find significant differences between subgroups of natural extracts of marijuana (THC, CBD, combination of THC and CBD) and synthetic cannabis (ajulemic acid, nabilone, dronabinol) on pain reduction or adverse events between. 50…”
Section: Can Cannabinoids Treat Chronic Musculoskeletal Pain?mentioning
confidence: 99%
“…These targets are found in the gastric mucosa, the enteric nervous system, and the immune system. Endocannabinoids, such as anandamide and 2-arachiodioylglycerol are molecules related to intercellular lipid signaling resulting from the demand for membrane precursors [32][33][34]. The increasing rates of patients with UC or CD have increased the search for therapies to patients that are refractory to conventional therapy, and that exhibit fewer side effects.…”
Section: Cannabis Sativa and Endocannabinoid Systemmentioning
confidence: 99%